Nilai Sosial Dalam Novel Isinga Roman Papua Karya Dorothea Rosa Herliany: Tinjauan Sosiologi Sastra Serta Implementasinya Dalam Pembelajaran Sastra Di Smk Muhammadiyah 10 Masaran - Saputra, Edi, Drs. Adyana Sunanda, M. Pd (2016)
This study aims to describe (1) the structure of the builders in the novel Isinga Roman Papua works of Dorothea Rosa Herliany (2) the social value of the novel Isinga Roman Papua works of Dorothea Rosa Herliany, (3) the implementation of the social value of the novel Isinga Roman Papua works of Dorothea RosaHerliany in literaturelearning in SMK Muhammadiyah 10 Masaran. This research is a descriptive qualitative case study research strategy rooted (embeddle case study). It can be concluded as follows: This novel theme of struggle and romance. This novel used progressive plot. The main character (protagonist) named Irewa, antagonists (Malom),tritagonis (Meage), and additional characters consisting of Jingi, Mama Kame, Labobar Father, Meage, Mama Fos, Ulunggi Father, doctor Leon, Wawutu Sister, Sister Karolin, Lepi, and Ms. Selvi. The title of the novel is Isinga Roman Papua. Setting on this novel consists of setting the place, time, and social. Point of view used in this novel is a third-person perspective is limited. Thestyles of this novel aresimple, straightforward, and easy to understand. The language used is not convoluted and tends to directly enter the author's intention is to be conveyed. While the tone is the emotional attitude of the authors featured in the story. Author of the novel conveysher emotions appropriately, are like feeling sad, happy, love, hope, fear, and anger. In this novel there are two symbols, the first, a symbol with the use of the term ceremony 'wit or initiation' ceremony and 'muruwal' included in this type of a symbol that appears on an important event in the story shows the meaning of the event. Second, a symbol with the use of the term 'betatas' is included in the symbol that appears in different contexts will help us find a theme. This novel use of dramatic irony or plot irony. In the novel there aresocial values of Isinga Roman Papua consists of the value of dedication, mutual help, family, loyalty, caring, sense of values, discipline, empathy, fairness, tolerance, cooperation, and democracy.The result be handout for teaching material.